IMPLEMENTASI KEBIJAKAN REHABILITASI SOSIAL PENYANDANG TUNA GRAHITA DI PANTI SOSIAL BINA GRAHITA NIPOTOWE PALU - Hanafi, Hanafi (Katalogis, 2015)
This study aimed to analyze the implementation of the policy of the Social Rehabilitation of Persons with Tuna Grahita in Panti Sosial Bina Grahita Nipotowe Palu, as well as supporting and inhibiting factors. Methods: The qualitative research with descriptive method, the informant as much as 7 people and are selected based on purposive sampling. Data collection techniques with interview, observation and documentation. Results of the study explained that, the implementation of rehabilitation policy of mentally disabled persons. because of the four dimensions studied, there is one dimension that implementation is not maximized, namely: first communication, especially the aspect of socialization maximum, second, human resources quality is adequate but the quantity is still lacking, infrastructure and funding shows the results sufficient for implementation of the policy, namely the third disposition implementer support and attitude regarding honesty, democratic nature and a commitment has been executed by the implementer, but not maximized, so that the implementation is less effective. While the bureaucratic structure that is SOP and the division of tasks was clear, so there is no fragmentation, and be flexible. Factors that inhibit the lack of professiona lhuman resources